2005
DOI: 10.1093/cercor/bhj007
|View full text |Cite
|
Sign up to set email alerts
|

Increased Neural Efficiency with Repeated Performance of a Working Memory Task is Information-type Dependent

Abstract: Unlike tasks in which practice leads to an automatic stimulus-response association, it is thought working memory (WM) tasks continue to require cognitive control processes after repeated performance. Previous studies investigating WM task repetition are in accord with this. However, it is unclear whether changes in neural activity after repetition imply alterations in general control processes common to all WM tasks or are specific to the selection, encoding and maintenance of the relevant information. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 21 publications
5
66
2
1
Order By: Relevance
“…Here, a key goal was to investigate the extent to which practice may play a role in "typical" non-practice fMRI studies, when subjects are not intentionally trying to improve their skills, but studies of task learning have used a variety of intentional learning paradigms, sometimes with scanning sessions occurring before and after an extended period of task practice. Studies using both motor and non-motor tasks have shown expansions in the cortical area engaged by the learned task after days or weeks of practice (Karni et al 1995, Olesen et al 2004, which is considerably different from the within-session decreases in activation that we and others have reported (Garavan et al 2000, Landau et al 2004, Sayala et al 2006. Thus, the implications of our results may not extend to longer time frame of practice, since short-term and long-term practice may engage different types of neural mechanisms (Karni et al 1998, Landau & D'Esposito 2006, although this issue clearly warrants further investigation.…”
Section: Temporal Dynamics Of Experience-dependent Wm Networkcontrasting
confidence: 57%
See 2 more Smart Citations
“…Here, a key goal was to investigate the extent to which practice may play a role in "typical" non-practice fMRI studies, when subjects are not intentionally trying to improve their skills, but studies of task learning have used a variety of intentional learning paradigms, sometimes with scanning sessions occurring before and after an extended period of task practice. Studies using both motor and non-motor tasks have shown expansions in the cortical area engaged by the learned task after days or weeks of practice (Karni et al 1995, Olesen et al 2004, which is considerably different from the within-session decreases in activation that we and others have reported (Garavan et al 2000, Landau et al 2004, Sayala et al 2006. Thus, the implications of our results may not extend to longer time frame of practice, since short-term and long-term practice may engage different types of neural mechanisms (Karni et al 1998, Landau & D'Esposito 2006, although this issue clearly warrants further investigation.…”
Section: Temporal Dynamics Of Experience-dependent Wm Networkcontrasting
confidence: 57%
“…In other words, the improvement in reaction times is most likely primarily due to increasing neural efficiency related to encoding processes, and secondarily, to retrieval processes. However, several studies have shown that practice-related changes in activation are not necessarily accompanied by changes in behavioral performance (Landau et al 2004, Olesen et al 2004, Sayala et al 2006, indicating that it is not possible to determine a clear link between the activation decreases and the faster reaction times.…”
Section: Practice and Behavioral Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Repetitive working memory training alone shows stimulus-specific practice effects (Sayala et al, 2006), yet we found significant functional changes that were not stimulus specific. In both tasks, improved behavioral performance was correlated with increased functional activity in a subset of the regions.…”
Section: Discussionmentioning
confidence: 59%
“…Decreased functional activations were observed by Jansma et al 12 after practice on a verbal Sternberg task, Sayala et al 13 after practice on an object/spatial working memory task, and Hempel et al 14 after practice on an n-back task. Decreases in functional activations have also been observed after practice on other types of higher cognitive task, such as the Tower of London problem 15 and tests of verbal free recall.…”
mentioning
confidence: 89%